Review: After the Evil. Christianity and Judaism in the Shadow of the Holocaust - Hannah Holtschneider, K. (The journal of theological studies, 2004)
After the Evil. Christianity and Judaism in the Shadow of the Holocaust Richard Harries Pp. x + 239 Oxford Oxford University Press 2003 0 19 926313 2 £16.99